Efficacy of Castor Oil as a Biopesticide for Treatment of Leucinodes orbitalis Guenee L., a Pest of Eggplant (Solanum melongena) - Mariame, Camara Mamadi; Windinpsidi, Savadogo Paul; Lanciné, Sangaré (Research Advances and Challenges in Agricultural Sciences Vol. 5, 2024)
Leucinodes orbonalis Guenee L. is a pest of eggplant. It is currently managed using synthetic chemical s. However, certain plants with insecticidal properties can be used to control Leucinodes orbonalis in eggplant. To study the efficacy of the castor oil solution on Leucinodes orbonalis, a trial was carried out at the ISAV in Faranah from 08/05 to 20/08/2023.Castor oil was extracted using a press machine with a yield of 0.41 l/kg. It was carried out at the station and in the laboratory. The experimental set-up used was a complete randomised block design with four replicates and five treatments. The treatments were D0 = 0 l/ha (control); D1 = 2.5 l/ha; D2 = 5 l/ha and D3 = 7.5 l/ha. The parameters monitored were: incidence of attack, number of plants leafed out and productivity. The survival of Leucinodes orbonalis larva after treatment was also estimated in vitro. The results showed that the incidence of attack after treatment was 68% for the control. However, this incidence was 10, 4 and 2% for doses D1, D2 and D3 respectively. With regard to the number of leafless plants, the rates were 68% for the control, 33% for D1, 17% for D2 and 8% for D3. Productivity was: 3.00 t/ha for the control; 5.00 t/ha for D1; 8.00 t/ha for D2 and 11.02 t/ha for D3. Survival of Leucinodes orbonalis larvae after application of the castor oil solution was 92%, 20%, 10% and 0% respectively for the control, D1, D2 and D3. Analysis of the results shows that the 7.5 l/ha dose of castor oil can be a good biopesticide for controlling Leucinodes orbonalis.